CORPORATE TAX MANAGEMENT: ESSENCE, TASK AND PRINCIPLES OF FUNCTIONING - Магопець, Олена; Бондарєв, Михайло (Modern engineering and innovative technologies, 2023)
According to the results of the conducted research, the essence of the concept of "corporate tax management" was determined - it is a set of methods, techniques and ways of managing the tax activities of a business entity, which is aimed at reducing the